El juego y la motricidad gruesa en los niños de 4 a 5 años del centro educativo inicial Crecer ubicado en la ciudad de Loja, período 2019 – 2020 - Calderón Cevallos., Johanna Pamela (2021)
This research was part of the project of the Child Psychology and Early Childhood Education major which was proposed in public and private educational institutions along with the students. The general objective was to analyze the importance of games and their effects in gross motor skills in children ages four to five. The research design was nonexperimental with a mixed approach. As being part of a macro project, information was collected from 31 institutions and 465 children. In particular, a population of 16 people was considered, and a sample of six children and two teachers were selected through nonprobabilistic sampling. The methodology used was descriptive, analytical-synthetic and inductive-deductive. Some of the techniques included: observation, application of a survey to the teachers, and application of the development abbreviated scale of Nelson Ortiz. Its application helped to determined that 67 % of children had difficulties in the gross motor area, having complications when performing activities such as walking in a straight line, taking three or more steps on a single foot, and bouncing and catching a ball; all these rooted in the lack of stimulation and confined spaces. This results led to the conclusion that 100 % of teachers apply learning experiences, workshops and learning corners as didactic strategies whereas they play games as fun activities without any specific purposes.